Autonomous Wintertime Observations of Air‐Sea Exchange in the Gulf Stream Reveal a Perfect Storm for Ocean CO2 Uptake. Issue 5 (1st March 2022) - Nickford, S.; Palter, J. B.; Donohue, K.; Fassbender, A. J.; Gray, A. R.; Long, J.; Sutton, A. J.; Bates, N. R.; Takeshita, Y.
Abstract: A scarcity of wintertime observations of surface ocean carbon dioxide partial pressure ( p CO2 ) in and near the Gulf Stream creates uncertainty in the magnitude of the regional carbon sink and its controlling mechanisms. Recent observations from an Uncrewed Surface Vehicle (USV), outfitted with a payload to measure surface ocean and lower atmosphere p CO2, revealed sharp gradients in ocean p CO2 across the Gulf Stream. Surface ocean p CO2 was lower by ∼50 μatm relative to the atmosphere in the subtropical mode water (STMW) formation region. This undersaturation combined with strong wintertime winds allowed for rapid ocean uptake of CO2, averaging −11.5 mmol m −2 day −1 during the February 2019 USV mission. The unique timing of this mission revealed active STMW formation. The USV proved to be a useful tool for CO2 flux quantification in the poorly observed, dynamic western boundary current environment. Plain Language Summary: The North Atlantic Ocean absorbs more atmospheric carbon dioxide (CO2 ) than most regions of the global ocean. Using an ocean drone in the Gulf Stream region during the winter of 2019, we measured the air‐sea CO2 difference, calculated the air‐sea CO2 exchange, and compared our results to previous wintertime ship‐based measurements. We find that the region south of the Gulf Stream can absorb vast amounts of atmospheric CO2, owing both to surface ocean properties and the strong wintertime winds. Because of extremely sparse wintertime observations in this region, we hypothesize that ocean uptake of CO2 may be underestimated. Our work suggests that ocean drones can help close the observational gaps that create uncertainty in ocean carbon uptake in challenging regions and seasons, if these vehicles and the sensors they carry can be made robust to large breaking waves. Key Points: Surface waters in the subtropical mode water formation region are lower in p CO2 than in the atmosphere in winter by ∼50 μatm Strong wintertime winds drive atmospheric CO2 into the ocean near the Gulf Stream with high spatial and temporal variability Uncrewed surface vehicles provide an opportunity to refine quantification and understanding of CO2 exchange near western boundary currents